Karyotypes of Manatees: New Insights into Hybrid Formation (Trichechus inunguis × Trichechus m. manatus) in the Amazon Estuary - Noronha, Renata C. R.; Almeida, Bruno R. R.; Chagas, Monique C. S.; Tavares, Flávia S.; Cardoso, Adauto L. [UNESP]; Bastos, Carlos E. M. C.; Silva, Natalia K. N.; Klautau, Alex G. C. M.; Luna, Fábia O.; Attademo, Fernanda L. N.; Lima, Danielle S.; Sabioni, Luiz A.; et al. (MDPI, 2022)
Great efforts have been made to preserve manatees. Recently, a hybrid zone was described between Trichechus inunguis (TIN) and the Trichechus manatus manatus (TMM) in the Amazon estuary. Cytogenetic data on these sirenians are limited, despite being fundamental to understanding the hybridization/introgression dynamics and genomic organization in Trichechus. We analyzed the karyotype of TMM, TIN, and two hybrid specimens (“Poque” and “Vitor”) by classical and molecular cytogenetics. G-band analysis revealed that TMM (2n = 48) and TIN (2n = 56) diverge by at least six Robertsonian translocations and a pericentric inversion. Hybrids had 2n = 50, however, with Autosomal Fundamental Number (FNA) = 88 in “Poque” and FNA = 74 in “Vitor”, and chromosomal distinct pairs in heterozygous; additionally, “Vitor” exhibited heteromorphisms and chromosomes whose pairs could not be determined. The U2 snDNA and Histone H3 multi genes are distributed in small clusters along TIN and TMM chromosomes and have transposable Keno and Helitron elements (TEs) in their sequences. The different karyotypes observed among manatee hybrids may indicate that they represent different generations formed by crossing between fertile hybrids and TIN. On the other hand, it is also possible that all hybrids recorded represent F1 and the observed karyotype differences must result from mechanisms of elimination.
Keywords: hybridization; karyotype; repetitive DNA; sirenia